2002
DOI: 10.1046/j.1440-169x.2002.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Blastopore formation and dorsal mesoderm induction are independent events in early Cynops embryogenesis

Abstract: The independent roles of blastopore formation and dorsal mesoderm induction in dorsal axis formation of the Cynops pyrrhogaster embryo were attempted to be clarified. The blastopore-forming (bottle) cells originated mainly from the progeny of the mid-dorsal C and/or D blastomeres of the 32-cell embryo, but were not defined to a fixed blastomere. It was confirmed that the isolated dorsal C and D blastomeres autonomously formed a blastopore. Ultraviolet-irradiated eggs formed an abnormal blastopore and then did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…(K) When the LDMZ is combined with a small piece of animal cap ectoderm, the animal cap ectoderm is induced to notochord (Nt) and muscle cells (Mus), while LDMZ itself differentiates into a mass of endodermal cells. Suzuki et al, 2002), while the notochord-inducing activity of the LDMZ remains active . Suzuki et al (2002) treated Cynops embryos with anti-morphogenesis reagents such as suramin (aspecific FGF-inhibitor, Gerhart et al, 1991;Grunz, 1992;Oschwald et al, 1993;Cardellini et al, 1994;Wallingford et al, 1997;Kaneda et al, 2002;Sakaguchi et al, 2002) or nocodazole (inhibitor for microtubule polymerization, Lane and Keller, 1997).…”
Section: Is Bottle Cell Formation Coupled With Mesoderm Induction?mentioning
confidence: 96%
See 1 more Smart Citation
“…(K) When the LDMZ is combined with a small piece of animal cap ectoderm, the animal cap ectoderm is induced to notochord (Nt) and muscle cells (Mus), while LDMZ itself differentiates into a mass of endodermal cells. Suzuki et al, 2002), while the notochord-inducing activity of the LDMZ remains active . Suzuki et al (2002) treated Cynops embryos with anti-morphogenesis reagents such as suramin (aspecific FGF-inhibitor, Gerhart et al, 1991;Grunz, 1992;Oschwald et al, 1993;Cardellini et al, 1994;Wallingford et al, 1997;Kaneda et al, 2002;Sakaguchi et al, 2002) or nocodazole (inhibitor for microtubule polymerization, Lane and Keller, 1997).…”
Section: Is Bottle Cell Formation Coupled With Mesoderm Induction?mentioning
confidence: 96%
“…In Xenopus, bottle cells are progressively formed by cells of the lower half of the suprablastoporal endoderm layer around the entire circumference of the marginal zone, but neither bottle cells nor the blastopore forms on the ventral side in Cynops (Doi et al, 2000). Cell lineage analyses have suggested that blastopore (bottle cell)-forming activity is not always defined in a particular blastomere at the cleavage stage in either urodeles or Xenopus (Holtfreter, 1944;Nakamura and Kishiyama, 1971;Doucet-de Bruïne, 1973;Smith and Slack, 1983;Gimlich, 1985;Takasaki, 1987;Hardin and Keller, 1988;Bauer et al, 1994;Suzuki et al, 2002), indicating that the bottle cells are induced before the onset of gastrulation. It can therefore be assumed that bottle cell induction and mesoderm induction occur in a temporally synchronized manner.…”
Section: Is Bottle Cell Formation Coupled With Mesoderm Induction?mentioning
confidence: 99%